Description on analyzing of forces acting on connection rod for various composite materials. (2021) - Kumar Singh, Pradeep; Chaturvedi, Rishabh; Islam, Anas
Abstract: Connecting rod is a significant component of entire assembly engine that acts by mediator among piston assembly and crankshaft. It's changing over the responding movement of the cylinder to turning movement of the wrench; likewise it faces a ton of tractable and compressive burdens during its life time. By and large associating poles are produced utilizing carbon steel and lately aluminum amalgams are discovering its application in interfacing bar. In this work associating bar is supplanted by aluminum and it additionally portrays the displaying and thermal examination of interfacing pole. Catia strong demonstrating programming is utilized to create the 3-D strong model of Connecting bar. Ansys programming is utilized to dissect the interfacing pole. The primary point of the project is to examine the thermal stress of connecting rod by changing material with same geometry.